On the identity of the Teyde dog-rose (Rosaceae): evidence for a new endemic taxon from Tenerife, Spain - Weller, André-Alexander; Reichert, Hans (Phytotaxa, 2023)
In view of the high diversity found in many groups of vascular plants on the Canary Islands, Spain, the genus Rosa (Rosaceae) is poorly represented comprising only two native taxa (R. canina, R. rubiginosa). For the first time, this study provides detailed data on distribution, morphology, chorology and status of the so-called ‘Teyde dog-rose’, a representative of the Section Caninae, which occurs exclusively in the subalpine zone of the Cañadas del Teide, Tenerife. A survey of both native stock and herbarium material yielded that this population, currently classified as common dog-rose (Rosa canina L.), is phenotypically close to continental representatives of the glaucous dog-rose (Rosa dumalis Bechst.), from which, however, it differs in several traits such as floral characters and leaf morphology. Consequently, the population is formally recognized as a distinct taxon, Rosa dumalis ssp. nov. teydensis Weller & H. Reichert. The new subspecies appears to be extremely rare in the wild, with a low number of individuals growing at scattered localities mainly at shady rocky walls and adjacent habitats in a restricted area of the southern Cañadas. Consequently, according to IUCN criteria the taxon must be regarded as Critically Endangered.